Mexico : Report on the Observance of Standards and Codes-FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT). (IMF Staff Country Reports; Country Report ;, 2018)
This report evaluates the observance of standards and codes on Financial Action Task Force recommendations for anti-money laundering and combating the financing of terrorism (AML/CFT) in Mexico. Mexico has a mature AML/CFT regime, with a correspondingly well-developed legal and institutional framework. The financial sector demonstrates a good understanding of the primary money laundering threats from organized crime groups and associated criminal activities as well as tax crimes, but the recognition of corruption as a main threat is uneven. Mexico also has a solid legal and institutional framework in place to seek and provide mutual legal assistance and extradition. The authorities also frequently rely on other forms of international cooperation to exchange information with other countries.